Learning Hangul Character Via Adventure Game / Nurizzati Aliah Jantan ... [et al.] - Jantan, Nurizzati Aliah; Mohd Radzi, Muhammad Hamiz; Che Haron, Mohammad Bakri; Saman, Fadhlina Izzah (2021)
The closure of public places such as schools and universities make learning in physical settings shifted to online learning since the Covid-19 outbreak. Most of the students are obliged to study at home with guidance from their instructors online. In some institutions, learning other than mother tongue is compulsory. Currently, the popularity of the Korean language has exploded in countries such as Malaysia. Most of the learning materials provided to learn Korean language are through books. However, people do not want to learn by books today, since they are used to digital and various types of technology. Learning a language will not be enjoyable without having an element of a game in the learning process. Enjoyment is one of the most important elements in learning the language to attract learners. Hence, the project aims to provide learning Hangul through game-based learning which implements Game Development Life Cycle (GDLC) model to develop the game. The scope for this project covered all forty letters of Hangul characters which they need to navigate the characters to answer some Hangul characters related questions to finish the mission given. The target user for the application is general to those who are interested in learning the Korean language, especially teenagers. EGameFlow model is then being used to evaluate the enjoyment of the user when playing this game as their tool for learning. The result gives a value of mean score 4.25 of 5.00, which shows that the application was enjoyable because it has exceeded 4.00 score, which shows that this application can be one of the learning tool alternatives that can be used to practice the Korean language in an enjoyable way.